Vransisca Kissya, Strategi Komunikasi Dalam Perumusan Program Promosi Dinas Parawisata Kota Ambon - Vransisca Kissya (STIA Abdul Azis Kataloka Ambon, 2020)
In Maluku, the tourism sector has a very good prospect. Besides having a wide range of cultures, Maluku with island character has beautiful beaches with stunning sea views. One of the tourist sites that became a beach tourism icon in the city of Ambon City Pintu City Beach offers a beach with a stretch of coral facing the sea with a door-like hole. Research Objective is to know Communication Strategy in formulation of tourism promotion programs at the object of maritime tourism Coast of Pintu Kota City in Ambon City and know effort which have been done by government to development maritime tourism Beach Door town, Ambon City. This research uses qualitative descriptive method, which is limited research on efforts to express a problem or situation or event as it is so just to reveal facts. The result of research shows that the persuasive communication approach done in the promotion, especially the promotion of beach tourism at Pantai Pintu Kota by the Local Government of Ambon City in this case the Tourism Department has not been done maximally. Besides, in terms of physical management, the Department of Tourism has not taken any strategic steps either legally. Dissemination of information about tourism potential by the Tourism Department has not been done maximally, budget constraints cause the lack of availability of media campaigns both print media and outdoor media, in addition to the catalogs about the profile of each tourism potential is not yet available properly.